საქართველოს საკითხი წამყვან სახელმწიფოთა საგარეო პოლიტიკაში XX საუკუნის პირველ მეოთხედში - Varshalomidze, Archil (Politics / პოლიტიკა, 2019)
The processes occurring in the world politics of the first half of the 20 th century, which were the result of the First World War serious consequences, were reflected in Transcaucasia, including Georgia. After all this, the country has become the geostrategic struggle between Russian i.e. the Soviet government and the Western countries. Even in the course of peace conference new tendencies were outlined in Batumi. The imperialistic policy of Turkey became unacceptable for Germany. Such changes in foreign policy of Germany had been caused by the fact that Georgia carried out the function of the bridge between Europe and Asia. In May 26 1918, the National Council was held, which declared the independence of Georgia. National government realized that if they could not get the recognition of Georgian independence from Russia, there would be less possibility for the leading European countries to recognize it either. For this reason, G. Khundadze was dispatched for the diplomatic mission to Russia, who did his best to make Russia recognize Georgian independence. In May 7 1920, the peace treaty was signed between Georgia and Russia. It was the step backwards in the development of the Georgian State system. Besides, it had the big strategic value better to supervise both Persia and the Caspian Sea, and Afghanistan. Defeat of Germany in the First World War put new geostrategic interests in front of Europe. Thus, Georgia and all Transcaucasia appeared under the influence of Great Britain. The young Georgian democratic republic had to conduct diplomatic struggle on two fronts - on the one hand, the Versailles conference and the issue of Georgia in the Nations League, and on the other hand - a heavy political situation in the district of Batumi. In spite of the crash on the discussion of Georgia at the Nations League, it still had positive outcomes. On January 27 1921, the Western countries recognized democratic Georgia de jure. However, on February 25 1921, Georgia was annexed by the Soviet Union, and it caused the problems concerning integration of Georgia with Europe for 70 years.
Keywords: Batumi, Conference, Transcaucasia, Frontier, Government, Annexed, World War, Development